Influence of methane emissions on the GHG emissions of fossil fuels. (18th December 2018) - Pieprzyk, Björn; Hilje, Paula Rojas
Abstract: Our study examines the effects of methane emissions on the greenhouse gas (GHG) emissions of crude oil and natural gas between 2015 and 2040. Our scenario calculations, derived from global methane budgets and shale analyses, provided a range of 22–59 million tons of global methane emissions from the oil sector in 2015. By 2040, the methane emissions of crude oil will increase by between 18% and 59%. For the global warming potential over 100 years (GWP100), our analysis shows venting, flaring, and fugitive (VFF) emissions of global diesel and gasoline combined of between 8.78 and 14.80 g CO2eq MJ −1 in 2015 and 8.88 to 16.34 g CO2eq MJ −1 by 2040. Our minimum average values for VVF emissions of fossil fuels are thus twice as high as those used in the calculations for the fossil reference value used in the Fuel Quality Directive of the European Union (EU‐FQD). The VVF emissions from diesel and gasoline produced from shale oil will reach up to 26.84 g CO2eq MJ −1 and from shale natural gas liquids (NGL) up to 31.84 g CO2eq MJ −1 . Our maximum marginal values for the VVF emissions of fossil fuels are thus up to nine times higher than the VVF value for the EU‐FQD. Based on our calculations, the EU‐FQD reference value for conventional fossil diesel will increase from 95 g MJ −1 to between 99.16 and 105.06 g MJ −1 for the GWP100 and between 109.80 and 124.70 g MJ −1 for the global warming potential over 20 years (GWP20). Our results thus show that the previous reference values for fossil fuels are clearly too low because their assumptions for methane emissions are far too low. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd